HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN IBU MENGHADAPI KLIMAKTERIUM DI WILAYAH KERJA PUSKESMAS BERSERI PANGKALAN KERINCI TAHUN 2019 - Romlah, Siti (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Background : Climacteric is a transitional period between the end of the reproductive years and ends at the beginning of senium, around the age of 40-45 years. Climacteric signed with the state of estrogen start to fall giving rise to a variety of complaints. Specialized in climacteric women to need support from the people closest to such a family in order to get through this with a level of anxienty that is expected to be reduced. Purpose : To investigate the relationship of family support with anxienty women dealing climakteric at Puskesmas Berseri working area Pangkalan Kerinci Method : Observational that is used quantitative with design cross sectional. Research is done at Puskesmas Berseri working area Pangkalan Kerinci with a population of 520 people and used purposive sampling technic make us of data analysis univariate and bivariate. Result : Be based chi square test the result is there is relationship of family support with anxienty women dealing climakteric at Puskesmas Berseri working area Pangkalan Kerinci (Pvaluae=0,04). Conclusion : Family support related with anxienty women dealing climakteric at Puskesmas Berseri working area Pangkalan Kerinci. Keywords: Family Support, Anxienty, Climacteric